Sulforaphane inhibits gastric cancer stem cells via suppressing sonic hedgehog pathway. (4th July 2019) - Ge, Miaomiao; Zhang, Lu; Cao, Lina; Xie, Chunfeng; Li, Xiaoting; Li, Yuan; Meng, Yu; Chen, Yue; Wang, Xiaoqian; Chen, Jiaqi; Zhang, Qi; Shao, Jihong; et al.
Abstract: Sulforaphane (SFN) is the major component extracted from broccoli/broccoli sprouts. It has been shown to possess anti-cancer activity. Gastric cancer is common cancer worldwide. The objective of this work was to evaluate the inhibitory effect of SFN on gastric cancer by Sonic hedgehog (Hh) Pathway. The results found that tumorsphere formation and the expression levels of gastric cancer stem cells (CSCs) markers were significantly decreased after SFN treatment. SFN also exerted inhibitory effects by suppressing proliferation and inducing apoptosis in gastric CSCs. Intriguingly, SFN inhibited the activation of Sonic Hh, a key pathway in maintaining the stemness of gastric CSCs. Upregulation of Sonic Hh pathway diminished the inhibitory effects of SFN on gastric CSCs. Collectively, these data revealed that SFN could be a potent natural compound targeting gastric CSCs via suppression of Sonic Hh pathway, which might be an promising agent for gastric cancer intervention. Graphical Abstract: